All about science: philosophy, history, sociology and communication - Burguete, Maria; Lam, Lui (New Jersey World Scientific, 2014)
There is a lot of confusion and misconception concerning science. The nature and contents of science is an unsettled problem. For example, Thales of 2,600 years ago is recognized as the father of science but the word science was introduced only in the 14th century; the definition of science is often avoided in books about philosophy of science. This book aims to clear up all these confusions and present new developments in the philosophy, history, sociology and communication of science. It also aims to showcase the achievement of China's top scholars in these areas. The 18 chapters, divided into five parts, are written by prominent scholars including the Nobel laureate Robin Warren, sociologist Harry Collins, and physicist-turned-historian Dietrich Stauffer.(http://www.worldscientific.com/worldscibooks/10.1142/8778)
Keywords: Science; Science - Philosophy